PERGULATAN AGAMA DALAM PERUBAHAN BUDAYA: Merespon Perubahan Budaya Interaksi Masyarakat melalui Situs Jejaring Sosial - Bashith, Abdul (ULUL ALBAB Jurnal Studi Islam, 2012)
The present reality of modern life mainstreaming of information and interaction as a source of capitalization of the search values, like maintaining a fire. If the use is quite proportional, then the technology and information into one medium that can deliver the deep nature of human life. But on the other hand, information technology and human interaction can be bamboozling in understanding the reality of what happened. The phenomenon that is now implicated in the use of social networking. Regardless of what people do routine, always expressed, reflected and internalized into the social networking site. The existence of increasingly affirms the social networking site to meet the desires of the way humans interact, but not infrequently social networking is also capable of carrying humans to the space that is "gray" zone between private and public sectors.